2011
DOI: 10.1097/ans.0b013e31822723a3
|View full text |Cite
|
Sign up to set email alerts
|

Unwanted Unprotected Sex

Abstract: This exploratory study used the theory of reasoned action and the theory of gender and power to guide elicitation of partner-related impediments to condom use among 64 adolescent girls living in poor urban areas with high rates of HIV and partner abuse. About 53% indicated that they had experienced unwanted, unprotected vaginal sex and 25% indicated that they were unable to discuss condom use with a partner. Novel qualitative findings related to condom coercion, condom sabotage, and self-silencing of condom ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 30 publications
2
64
0
Order By: Relevance
“…Furthermore, our findings indicated that for young women who had little control over their safe sex decisions, negative test results made it more difficult to negotiate condom use, further undermining one of the most effective risk reduction strategies. These findings are consistent with those of other studies that have shown that abusive and controlling relationship dynamics tend to restrict young women's ability to negotiate for condom use or mutual monogamy, thereby increasing HIV risk 16,18,23,24,26 . Recognizing this increased STI/HIV risk, these young women chose to negotiate for HIV/STI testing because it was the only risk reduction tool their partners would agree to.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, our findings indicated that for young women who had little control over their safe sex decisions, negative test results made it more difficult to negotiate condom use, further undermining one of the most effective risk reduction strategies. These findings are consistent with those of other studies that have shown that abusive and controlling relationship dynamics tend to restrict young women's ability to negotiate for condom use or mutual monogamy, thereby increasing HIV risk 16,18,23,24,26 . Recognizing this increased STI/HIV risk, these young women chose to negotiate for HIV/STI testing because it was the only risk reduction tool their partners would agree to.…”
Section: Discussionsupporting
confidence: 91%
“…Often occurring as a result of gender power imbalances between men and women, such circumstances often leave women in choice-restricted relationships with limited sexual relationship power, or control over one's sexual decision-making 16 . This type of partner abuse is a form of sexual coercion that can manifest as unwanted unprotected sex with a partner who has other partners or other forms of active interference by a partner with safer sex practices 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that gender inequitable norms may have a higher impact on the behaviour of fathers. In a context of uneven power dynamics within heterosexual sexual scenarios, it can often be the case that the attitudes and beliefs of the male partner will determine whether or not condoms will be used, even if condom use is the desired outcome for the female partner (Teitelman, Tennille, Bohinski, Jemmott, & Jemmott, 2011;Tschann et al, 2002). This may explain why even though mothers had attitudes that were more supportive of gender equity, it did not seem to have an impact on whether they used a condom the last time that they had sex.…”
Section: Discussionmentioning
confidence: 99%
“…Coercive CUR involves situations in which the woman has consented to sexual intercourse, but it is predicated on the use of a condom, thus differentiating these behaviors from those which meet the legal definition of sexual assault. However, similar to sexual assault, coercive CUR behaviors threaten women's sexual safety and take away women's ability to protect themselves from STI/HIV infection and unplanned pregnancy (Teitelman, Tenille, Bohinski, Jemmott, & Jemmott, 2011; Thiel de Bocanegra, Rostovtseva, Khera, & Godhwani, 2010). The goal of the current research is to identify how men's intentions to use coercive CUR tactics differ based on individual (e.g., hostility toward women) and situation-specific risk factors (beverage condition: alcohol vs. sober control), and different condom use requests styles.…”
Section: Introductionmentioning
confidence: 99%